Efektivitas Model Discovery Learning Dalam Meningkatkan Keaktifan Belajar Siswa Pada Pembelajaran IPS Terpadu Di Kelas VIII H SMP Negeri 1 Bendosari SukoharjoTahun Pelajaran 2015/2016 - Azmi, Kemala Uli; Suwandi, SE.,M.Pd, Drs. Joko Suwandi, SE.,M.Pd (2016)
This study aims to improve students' learning activeness using Discovery Learning Strategy H class VIII student in the teaching of economics in Junior High School 1 Bendosari in academic year 2015/2016. This study is classroom action research (PTK). This classroom action research is qualitative data jenia, Taitu data in the form words, sentences and schemes. The research subject is class VIII H Junior High School 1 Sukoharjo Bendosari academic year 2015/2016. Methods of data collection using the method of observation, interviews, field notes, documentation. The procedures in this study there are five stages: the initial dialog, class action planning, action, observation, reflection and evaluation. Data analysis technique used is the technique of critical and comparative techniques. The results of this study indicate that the application of Discovery Learning strategies can improve students' learning activeness. It can be seen from: 1) To participate in carrying out the task of learning, 2) inquiry to other students or the teacher if it does not understand the problems it faces, 3) Trying to find a variety of information necessary for solving the problem, 4) Conducting group discussions in accordance with user teachers, 5) Assess the ability of himself and the results obtained. This means research that has been conducted by researchers collaborating with teachers of economic subjects, increased activeness of student learning at the end of the first cycle of 59.37%. In the second cycle students' learning activeness increased by 77.49%. By this means an increase in students' learning activeness exceeds the indicators of success, namely 75%. Based on the research data it can be concluded that the application of the Discovery Learning strategies can enhance the activity of class VIII H SMP Junior High Schoo1 Sukoharjo Academic Year 2015/2016.